Controllable deformation based self‐adaptive drag reduction for complex surface. Issue 1 (28th February 2023) - Chen, Dengke; Cui, Xianxian; Chen, Huawei
Abstract: Reduction of energy consumption and improvement of cruising speed are greatly necessary for underwater vehicles. Previously, regular riblets have been machined and the drag reduction has been verified; however, the riblet parameters are not adjusted like the denticles of sharkskin, which adapt quickly to the complex changing fluid flow. To achieve an improved drag reduction effect on the complicated shape surface, a simple, low‐cost, and timesaving stretching approach was proposed to adjust the riblet parameters on the underwater vehicle surface by controllable deformation. Nature latex rubber membrane with regular micro‐riblets was prepared as a stretching flexible film, and the spacing and height of the micro‐riblets were adjusted by adaptive control of the stretching ratio. The circulating water channel experiment verified the effectiveness and feasibility of the self‐adaptive drag reduction by the controllable deformation method. The results demonstrated that the drag reduction rate of the controllable deformation bionic fish skin was 4.26% compared with a smooth surface at 0.25 m/s with an angle of attack of 0°, which is better than any other angle. The controllable deformation bionic fish skin provides a feasible method for the drag reduction of complex surface adaptive underwater vehicles.